2004
DOI: 10.1021/ma035295q
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Polymorphic Behaviors of Ziegler−Natta and Metallocene-Made Isotactic Polypropylene:  The Role of the Distribution of Defects in the Polymer Chains

Abstract: A comparative analysis of the polymorphic behavior of samples of isotactic polypropylene (iPP) prepared with heterogeneous Ziegler−Natta catalysts and with a single-center homogeneous metallocene catalyst is presented. Different samples of Ziegler−Natta iPP, prepared with MgCl2-supported catalysts modified by adding different Lewis bases, have been fractionated by extraction with boiling solvents. The irregular fraction, insoluble in diethyl ether and soluble in hexane, crystallizes from the melt almost totall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(144 citation statements)
references
References 44 publications
8
135
1
Order By: Relevance
“…These results are well in line with the outcome of the extensive investigations reported in the literature [29][30][31][32][33][34][35][36][37][38][39][40][41][42]49,50] on different polypropenes containing random regio, stereo and constitutional defects. The fractional content of gpolymorph strongly depends on the total concentration of defects and on crystallization temperature.…”
Section: Samplesupporting
confidence: 86%
See 1 more Smart Citation
“…These results are well in line with the outcome of the extensive investigations reported in the literature [29][30][31][32][33][34][35][36][37][38][39][40][41][42]49,50] on different polypropenes containing random regio, stereo and constitutional defects. The fractional content of gpolymorph strongly depends on the total concentration of defects and on crystallization temperature.…”
Section: Samplesupporting
confidence: 86%
“…[21][22][23][24] The availability of structurally well defined isotactic polypropenes has renewed the interest on the formation of the g-polymorph, which displays unique crystallographic structure [25,26] and is typical of polypropenes with short isotactic sequences. [11,27,28] The recent extensive investigations performed on propene homopolymers with various contents of regio and stereo defects and on random copolymers with 1-olefins by Alamo et al [29][30][31][32][33][34] and De Rosa et al [35][36][37][38][39][40][41][42] have shown that random constitutional defects essentially behave as any other type of irregular unit in the development of the g-polymorph. The amount of g-form was found to be strictly correlated with the length of isotactic sequences which, for randomly placement of mistakes, is inversely related to their total content.…”
Section: Full Papermentioning
confidence: 99%
“…The appearance of the different crystalline forms depends to a large extend on the chain microstructure, [20,21] processing conditions [22,23] and presence of specific nucleating agents. [24,25] However, under C. Hedesiu et al conditions as usually applied during industrial processing the a-form is always predominant.…”
Section: X-ray Resultsmentioning
confidence: 99%
“…[12][13][14][15] The results of these analyses are mainly dependent on stereoregularity of poly(propylene) and are almost independent of molecular weight. [16,17] This technique reveals even minor differences in stereoregularities of polymers prepared with similar catalysts.…”
Section: Introductionmentioning
confidence: 99%